2017
DOI: 10.3322/caac.21413
|View full text |Cite
|
Sign up to set email alerts
|

Key issues surrounding the health impacts of electronic nicotine delivery systems (ENDS) and other sources of nicotine

Abstract: Answer questions and earn CME/CNE Over the last decade, the use of electronic nicotine delivery systems (ENDS), including the electronic cigarette or e-cigarette, has grown rapidly. More youth now use ENDS than any tobacco product. This extensive research review shows that there are scientifically sound, sometimes competing arguments about ENDS that are not immediately and/or completely resolvable. However, the preponderance of the scientific evidence to date suggests that current-generation ENDS products are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 102 publications
1
52
0
3
Order By: Relevance
“…To evaluate the net public health benefit of ENDS, it is necessary to consider at least the following: 1) the harm from using ENDS, 2) the influence of ENDS on adult cigarette cessation, and 3) youth initiation of ENDS, leading either to long‐term ENDS use or to eventual combustible tobacco use. Major recent reviews concluded that the exclusive use of current‐generation ENDS is likely to be significantly less harmful than using combustible tobacco products (with or without concurrent use of ENDS), but there are not yet sufficient data to evaluate the long‐term health effects of using ENDS. Although carcinogens, including tobacco‐specific nitrosamines, are found in ENDS aerosol, the levels are significantly lower than those in tobacco smoke, and there are considerably fewer toxicants in ENDS aerosol compared with tobacco smoke .…”
Section: Tobacco Productsmentioning
confidence: 99%
“…To evaluate the net public health benefit of ENDS, it is necessary to consider at least the following: 1) the harm from using ENDS, 2) the influence of ENDS on adult cigarette cessation, and 3) youth initiation of ENDS, leading either to long‐term ENDS use or to eventual combustible tobacco use. Major recent reviews concluded that the exclusive use of current‐generation ENDS is likely to be significantly less harmful than using combustible tobacco products (with or without concurrent use of ENDS), but there are not yet sufficient data to evaluate the long‐term health effects of using ENDS. Although carcinogens, including tobacco‐specific nitrosamines, are found in ENDS aerosol, the levels are significantly lower than those in tobacco smoke, and there are considerably fewer toxicants in ENDS aerosol compared with tobacco smoke .…”
Section: Tobacco Productsmentioning
confidence: 99%
“…nickel, and lead; and particles of copper, nickel, and silver have been found in electronic nicotine delivery system aerosol in higher levels than in conventional cigarette smoke. 41 The specifi c chemicals detected can vary greatly between brands, even when the fl avoring and nicotine content are equivalent, which frequently results in inconsistent and confl icting study fi ndings. The chemicals detected also vary with the voltage or power used to generate the aerosol.…”
Section: ■ Bad Things In E-liquid Aerosolmentioning
confidence: 99%
“…Además, se estableció una edad mínima de compra de 18 años (aquellos estados con edades mínimas de compra mayor de 18 años no tienen que cambiarlas), presencia de etiquetado que advierta los potenciales riesgos para la salud y prohibición de su venta en máquinas expendedoras, a menos que estén en un lugar en el que no se acepten menores de edad a toda hora. Cabe aclarar que algunos estados son menos flexibles y establecen edades mínimas superiores (52,53,54).…”
Section: Cigarrillo Electrónico Y Salud Pública: Regulaciones Y Medidunclassified